Role of MyD88 signaling in the imiquimod‐induced mouse model of psoriasis: focus on innate myeloid cells. Issue 3 (22nd June 2017) - Costa, Sara; Marini, Olivia; Bevilacqua, Dalila; DeFranco, Anthony L.; Hou, Baidong; Lonardi, Silvia; Vermi, William; Rodegher, Pamela; Panato, Anna; Tagliaro, Franco; Lowell, Clifford A.; Cassatella, Marco A.; et al.
Abstract : MyD88 signaling in monocytes/macrophages sustains disease progression in the IMQ‐induced mouse model of psoriasis. Abstract : Psoriasis is a chronic skin disease associated with deregulated activation of immune cells and keratinocytes. In this study, we used the imiquimod (IMQ)‐induced mouse model of psoriasis to dissect better the contribution of hematopoietic and skin‐resident stromal cells to psoriasis development. The comparison of disease development in mice carrying the hematopoietic cell‐specific deletion of MyD88 ( Myd88 fl/fl Vav‐cre + mice) with mice carrying the total MyD88 deficiency ( Myd88 −/− mice), we show that the progression of skin and systemic inflammation, as well as of epidermal thickening, was completely dependent on MyD88 expression in hematopoietic cells. However, both Myd88 −/− mouse strains developed some degree of epidermal thickening during the initial stages of IMQ‐induced psoriasis, even in the absence of hematopoietic cell activation and infiltration into the skin, suggesting a contribution of MyD88‐independent mechanisms in skin‐resident stromal cells. With the use of conditional knockout mouse strains lacking MyD88 in distinct lineages of myeloid cells ( Myd88 fl/fl LysM‐cre + and Myd88 fl/fl MRP8‐cre + mice), we report that MyD88 signaling in monocytes and Mϕ, but not in neutrophils, plays an important role in disease propagation and exacerbation by modulating their ability to sustain γδ T cell effector functions via IL‐1β and IL‐23 production. Overall, these findings add new insights into the specific contribution of skin‐resident stromal vs. hematopoietic cells to disease initiation and progression in the IMQ‐induced mouse model of psoriasis and uncover a potential novel pathogenic role for monocytes/Mϕ to psoriasis development.